Implementation of the Saving Matrix Method to Determine Vehicle Routes - Rizkilah Ramdani, Willy; Rizwan, Rifan; Faisal Khobir, Muhammad; Fauzi, Muchammad (Green Publisher Indonesia, 2021)
The availability of the number of vehicles in Karawang Regency is not matched by the availability of fuel at gas stations. Due to the very high demand for fuel, the Cikampek BBM Terminal has several problems, including the absence of a standard distribution route in distributing its products to gas stations so that it takes a long time and the high amount of transportation costs that must be borne by the company. In this study, the route and distribution schedule will be determined as well as determining the capacity and number of tanker trucks that are able to minimize mileage, travel time and transportation costs. Based on calculations using the Saving Matrix method, it produces efficiency in the number of vehicles needed from 7 trucks to 4 tanker trucks, vehicle usage from 9 times to 6 times, distance traveled from 63 KM to 53 KM and the difference in transportation costs per day is Rp. 1,312,633.